PENERAPAN MODEL COOPERATIVE LEARNING TIPE JIGSAW UNTUK MENINGKATKAN TANGGUNG JAWAB DAN PRESTASI BELAJAR BAHASA INDONESIA (Sudi Siswa Kelas X SMA Negeri 1 Gumay Talang Kabupaten Lahat) - Hengki Saputra (UNIB Press, 2020)
This research was conducted with the aim to find out 1) The application of the Jigsaw cooperative learning model can increase student responsibility, 2) The application of the Jigsaw cooperative learning model can improve student learning achievement in Indonesian Language subjects in Students and 3) The effectiveness of the application of type cooperative learning models Jigsaw in improving student learning achievement in learning Indonesian Language Class X in SMA Negeri 1 Gumay Talang, Lahat Regency. The problem in this study is that the learning methods used are less varied, the low attitude of student responsibility in participating in learning. This study used 25 subjects in PTK research, 20 in experimental class research, and 20 people in control class research. Data collection techniques in this study used observation and tests. The results of this study indicate that the application of a Jigsaw cooperative learning model can increase student responsibility in Indonesian subjects, the application of a Jigsaw cooperative learning model can improve student learning achievement in Indonesian subjects, and the application of a Jigsaw cooperative learning model can effectively improve student learning achievement in Indonesian subjects class X in SMA Negeri 1 Gumay Talang, Lahat Regency.